Biofabrication and bioprinting using cellular aggregates, microtissues and organoids for the engineering of musculoskeletal tissues - Kelly, Daniel (My University, 2021)
The modest clinical impact of musculoskeletal tissue engineering (TE) can be attributed, at least in part, to a failure to recapitulate the structure, composition and functional properties of the target tissue. This has motivated increased interest in developmentally inspired TE strategies, which seek to recapitulate key events that occur during embryonic and post-natal development, as a means of generating truly biomimetic grafts to replace or regenerate damaged tissues and organs. Such TE strategies can be sub- stantially enabled by emerging biofabrication and bioprinting strategies, and in particular the use of cel- lular aggregates, microtissues and organoids as ‘building blocks’ for the development of larger tissues and/or organ precursors. Here, the application of such biological building blocks for the engineering of musculoskeletal tissues, from vascularised bone to zonally organised articular cartilage, will be reviewed. The importance of first scaling-down to later scale-up will be discussed, as this is viewed as a key com- ponent of engineering functional grafts using cellular aggregates or microtissues. In the context of engi- neering anatomically accurate tissues of scale suitable for tissue engineering and regenerative medicine applications, novel bioprinting modalities and their application in controlling the process by which cel- lular aggregates or microtissues fuse and self-organise will be reviewed. Throughout the paper, we will highlight some of the key challenges facing this emerging field.
Keywords: Microtissues; Spheroids; Biofabrication; Microtissues; Spheroids; Biofabrication